Knowledge level and associated factors about sexual and reproductive health rights among University of Gondar students, Gondar Ethiopia - Kefl ie Yohannes Gebresilassie; Moges Muluneh Boke; Melaku Kindie Yenit; Adhanom Gebreegziabher Baraki (International Journal of Sexual and Reproductive Health Care - Peertechz Publications, 2019)
Background: Young peoples' knowledge on sexual and reproductive health rights (SRHRs) is essential in exercising these rights. Knowledge about SRHRs helps tackling of neglected issues, such as adolescent sexuality, gender based violence, and unsafe abortion. But little is known about tshe level of knowledge and the important predictors in the study area, therefore this study was done to fi ll this information gap. Objective: This study aimed to assess knowledge about sexual and reproductive health rights and associated factors among undergraduate regular students in University of Gondar, 2018.